From religious association to ethnic community: a research project on identity formation among the Syrian Orthodox under Muslim rule - Haar Romeny, Robert Barend ter (Islam and Christian-Muslim relations, 2005)
At the Universityof Leiden, a research group is investigating the formation of a communal identity among West Syrian (or Syrian Orthodox) Christians after the Council of Chalcedon in 451 CE. Of the anti-Chalcedonians, the Syrian Orthodox were probably least likely to form a national or ethnic community. Yet a group emerged with its own distinctive literature and art, its own network and historical consciousness. In a process of adoption and rejection, the West Syrians selected elements from the cultures to which they were heirs and from those with which they came into contact, thus defining a position of their own. In order to study this phenomenon, scholars from various disciplines and affiliated to two different faculties are working together. This paper discusses their research programme and its basic hypothesis.